A study protocol for implementing Canadian Practice Guidelines for Treating Children and Adolescents with Eating Disorders - Couturier, Jennifer L.; Kimber, Melissa; Ford, Catherine; Coelho, Jennifer S.; Dimitropoulos, Gina; Kurji, Ayisha; Boman, Jonathan; Isserlin, Leanna; Bond, Jason; Soroka, Chelsea; Dominic, Anna; Boachie, Ahmed; et al. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background Eating disorders have one of the highest mortality rates among psychiatric illnesses. Timely intervention is crucial for effective treatment, as eating disorders tend to be chronic and difficult to manage if left untreated. Clinical practice guidelines play a vital role in improving healthcare delivery, aiming to minimize variations in care and bridge the gap between research and practice. However, research indicates an active guideline implementation approach is crucial to effective uptake. Methods Mixed methods will be used to inform and evaluate our guideline implementation approach. Semi-structured focus groups will be conducted in each of the eight provinces in Canada. Each focus group will comprise 8–10 key stakeholders, including clinicians, program administrators, and individuals with lived experience or caregivers. Qualitative data will be analyzed using conventional content analysis and the constant comparison technique and the results will be used to inform our implementation strategy. The study will then evaluate the effectiveness of our implementation approach through pre- and post-surveys, comparing changes in awareness, use, and impact of the guidelines in various stakeholder groups. Discussion Through a multifaceted implementation strategy, involving the co-creation of educational materials, tailored training, and context-specific strategies, this study intends to enhance guideline uptake and promote adherence to evidence-based practices. Our study will also contribute valuable information on the impact of our implementation strategies.

Lay Abstract This protocol outlines a comprehensive research study aimed at evaluating an implementation approach for the uptake of the Canadian Practice Guidelines for Treating Children and Adolescents with Eating Disorders across Canada. Eating disorders (EDs) have a significant impact on mental and physical health, necessitating evidence-based and timely interventions. To address gaps in service, we propose to use focus groups to identify barriers, facilitators, and implementation strategies for guideline uptake. We will engage stakeholders, including clinicians, administrators, and individuals with lived experience, to co-create tailored educational materials which will then be disseminated. The impact of the implementation approach will be evaluated through pre- and post-implementation surveys. This study aims to enhance the availability and utilization of evidence-based treatments for children and adolescents with EDs, ensuring equitable and improved care nationwide.